Pengaruh Prosedur Pemberian Kredit Terhadap Peningkatan Jumlah Nasabah - Muhammad Anas (Al-Buhuts, 2017)
Basically, credit is something mostly needed by the society that can supporting and running well the commerce activities, whether in goods productions, service and also improving or fulfilling the need of society consumption. The aim of this research is to analysis the provide credit facility, such as character, capacity, Capital, and the condition of economy towards some of bank customers of BRI Branch at Marisa in Pohuwato restrict. In this research it is used questionnaire that distributing towards 40 respondents in order to get information about the problems which being related to the variables observed. The analysis instrument used is multiple regressions. The result of this research showed that the research variable whether in a partial or simultaneous regression proved having positive influence and significantly towards improvement of BRI bank customers in Marisa at Pohuwato District.